2018
DOI: 10.1002/adem.201701116
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Grown Iron Oxides on Carbon Nanofibers as Freestanding Anodes in Aqueous Supercapacitors

Abstract: Iron oxides are promising materials for application in supercapacitors owing to their high theoretical redox capacitance (2299 F g À1 ). Nevertheless, iron oxide nanostructures experience constant stress during cycling due to repeated expansion and contraction resulting in structural degradation. Such structural instability makes it challenging to develop freestanding and binderfree iron oxide-based electrodes with superior electrochemical performance. In this work, the authors report a facile way to fabricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…Figure 2a shows the three different electrochemical windows of VOPO 4 •2H 2 O at a scan rate of 5 mVs -1 . In alkaline electrolytes, the electrochemical window is 1.0 V and in neutral electrolyte (3M LiNO 3 ) it can be extended up to 1.1 V. These ranges of potential agree with the reports from literature for aqueous electrolytes [4,24,33,34]. It is worthy to highlight the electrochemical response found from 5 up to 100 mVs -1 , that indicates a fast charge-discharge process for VOPO 4 •2H 2 O in these three electrolytes (see Figure SI2).…”
Section: Electrochemical Characterizationsupporting
confidence: 91%
“…Figure 2a shows the three different electrochemical windows of VOPO 4 •2H 2 O at a scan rate of 5 mVs -1 . In alkaline electrolytes, the electrochemical window is 1.0 V and in neutral electrolyte (3M LiNO 3 ) it can be extended up to 1.1 V. These ranges of potential agree with the reports from literature for aqueous electrolytes [4,24,33,34]. It is worthy to highlight the electrochemical response found from 5 up to 100 mVs -1 , that indicates a fast charge-discharge process for VOPO 4 •2H 2 O in these three electrolytes (see Figure SI2).…”
Section: Electrochemical Characterizationsupporting
confidence: 91%
“…For IP, deconvolution of O1s spectra produced two peaks located at 530.1 eV and 531.4 eV, corresponding to lattice-O 2À and -OH lat /C-O. 37,38 Aer TC and LEV adsorption, the ratio of -OH lat decreased from 34.38% to 27.52% and 26.62%, respectively. It indicated that the -OH lat was one of the functional groups in the adsorption process.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…44 The decrease in specific capacitance is due to the diffusion limitation and underutilization of the active material at higher specific currents. 45 The contribution of Ni foam substrate to the capacitances is found negligible. Importantly, for the application point of view, cyclic stability of an electrode material plays a significant role.…”
Section: Resultsmentioning
confidence: 86%